Justice Enforcement on Plans for Imposition of Value Added Tax on Premium Basic Necessities - Ayu Putri Rainah Petung Banjaransari (Law Department, Sharia and Law Faculty., 2021)
The plan to impose a value added tax (hereinafter referred to as VAT) on basic commodities has recently caused a polemic between the government and the community regarding justice and public welfare. The community is questioning the implementation of a just and civilized welfare from the government for the imposition of the VAT. Previously, on basic commodities, the government did not charge any kind of tax at all. The imposition of this tax is motivated by the economic recovery during the COVID-19 pandemic, Indonesia's VAT rate is too low, and the structure of state revenue is dominated by VAT. This paper aims to provide an analysis of the relationship between the imposition of VAT on staple goods and their impact on the level of community justice. The method used in this paper is a qualitative research method with a normative-juridical approach which is carried out through a literature study. This paper describes the findings related to the reasons for the government to charge VAT on basic necessities and the protection of the community's right to justice on the imposition of VAT. This finding can provide an overview for the continuation of the revision of the draft Law Number 6 of 1983 concerning General Provisions and Tax Procedures (hereinafter referred to as the KUP Bill) which contains revisions on basic materials as objects of VAT.